Dealer Behavior and Trading Systems in Foreign Exchange Markets - Geir Høidal Bjønnes; Dagfinn Rime (Norges Bank, 2003)
We study dealer behavior in the foreign exchange spot market using a detailed data set on the complete transactions of four dealers. There is strong support for an information effect in incoming trades. Although there is evidence that the information effect increases with trade size in direct bilateral trades, the direction of a trade seems to be more important. The large share of electronically brokered trades is probably responsible for this finding. In direct trades it is the initiating dealer that determines trade size, while in broker trades it is the dealer submitting the limit order that determines the maximum trade size. We also find strong evidence of inventory control for all the four dealers. Inventory control is not, however, manifested through a dealer's own prices as suggested in inventory models. This is different from the strong price effect from inventory control found in previous work by Lyons [J. Fin. Econ 39(1995) 321]. A possible explanation for this finding is that the introduction of electronic brokers allowed more trading options. Furthermore, we document differences in trading styles among the four dealers, especially how they actually control their inventories.
hdl:11250/2498617
Keywords: G15; F31; F33; 330; foreign exchange; trading; microstructure